Keindahan Saja’ Dalam Matan Tuḥfah Al-Aṭfāl Karya Sulaimān Al-Jamzūrī - Zahrotul Qotrunnada; Sayyed Zuhdi Abdil Ghany; Iin Suryaningsih (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
The Arabic language serves as a global communication tool and is the principal language for 2 billion Muslims across the globe. Within Arabic, there are diverse realms of discourse and academic pursuits. One such domain is the Science of Badīʿ, a branch of Balāghah (rhetoric). A key area within the Science of Badīʿ delves into the resemblance of the final letters of two words at the conclusion of Arabic sentence structures. This resemblance, termed